2018
DOI: 10.1364/oe.26.020298
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear refractive index of electric field aligned gold nanorods suspended in index matching oil measured with a Hartmann-Shack wavefront aberrometer

Abstract: The capability to dynamically control the nonlinear refractive index of plasmonic suspensions may enable innovative nonlinear sensing and signaling nanotechnologies. Here, we experimentally determine the effective nonlinear refractive index for gold nanorods suspended in an index matching oil aligned using electric fields, demonstrating an approach to modulate the nonlinear optical properties of the suspension. The nonlinear optical experiments were carried out using a Hartmann-Shack wavefront aberrometer in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The underlying mechanism for this phenomenon is not quite clear, though, and we believe it may be related to interactions between the soliton beam and the probe beam. In any case, it is with no doubt that nanorods can be aligned by high electric fields [18][19][20], so the proposed scheme in Fig. 5(b) and associated anisotropic optical properties should be achievable with intense optical beams under appropriate conditions.…”
Section: E Soliton-mediated Anisotropic Optical Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism for this phenomenon is not quite clear, though, and we believe it may be related to interactions between the soliton beam and the probe beam. In any case, it is with no doubt that nanorods can be aligned by high electric fields [18][19][20], so the proposed scheme in Fig. 5(b) and associated anisotropic optical properties should be achievable with intense optical beams under appropriate conditions.…”
Section: E Soliton-mediated Anisotropic Optical Propertymentioning
confidence: 99%
“…The collective alignment of a large quantity of gold nanorods in a liquid environment may lead to macroscopic anisotropic optical response and can find applications in information processing and display technologies. While ordering of an ensemble of rods has been demonstrated with techniques including applying electric fields [15][16][17][18][19][20], self-assembly based fabrication [21][22][23], the stretched-film method [24][25][26], and the electrospinning technique [27,28], so far only manipulation of individual plasmonic nanorods was demonstrated experimentally with optical traps [29][30][31][32][33][34]. Recently, we attempted to achieve orientational ordering of gold nanorods inside an optical soliton channel established by pumping a colloidal suspension of gold nanorods with a 532 nm laser beam [35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed important results, for example, in data storage, tunable random laser, and solar cell technology . The modulation, at 60 Hz, of the NL refractive index of gold nanorods (Au-NRs) suspended in oil was recently reported . Also, the enhanced NL absorption of aligned Au-NRs embedded in poly­(vinyl alcohol) films was demonstrated due to the plasmonic interaction among densely packed rods …”
Section: Introductionmentioning
confidence: 99%
“…For example, the possibility of nonlinearity management of plasmonic systems by selecting the appropriate nanoparticles concentration opens new routes for studies of high-order nonlinear optical phenomena and new spectroscopic investigations Reyna and de Araújo, 2015). The combination between nonlinear optics and electronics offers the possibility for dynamical control of metal nanorods for nonlinear sensing and signaling nanotechnologies as demonstrated in (Maldonado et al, 2018 and references therein). Random lasers have been optimized by inserting metal nanoparticles in the gain media and new advances in this area are possible by Note: From bottom to top the intensities are 0.4, 0.8, 1.6, 2.4, 3.2 and 4 GW/cm 2 .…”
Section: Discussionmentioning
confidence: 99%